2020
DOI: 10.5194/gmd-13-5007-2020
|View full text |Cite
|
Sign up to set email alerts
|

A new bias-correction method for precipitation over complex terrain suitable for different climate states: a case study using WRF (version 3.8.1)

Abstract: Abstract. This work presents a new bias-correction method for precipitation over complex terrain that explicitly considers orographic characteristics. This consideration offers a good alternative to the standard empirical quantile mapping (EQM) method during colder climate states in which the orography strongly deviates from the present-day state, e.g. during glacial conditions such as the Last Glacial Maximum (LGM). Such a method is needed in the event that absolute precipitation fields are used, e.g. as inpu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 112 publications
1
19
0
Order By: Relevance
“…come into equilibrium. Tests show that the WRF land surface scheme reaches a quasi-equilibrium after approximately 15 days (Velasquez et al, 2020). The initial and boundary conditions for WRF were provided by the global CCSM4 simulations.…”
Section: Introductionmentioning
confidence: 99%
“…come into equilibrium. Tests show that the WRF land surface scheme reaches a quasi-equilibrium after approximately 15 days (Velasquez et al, 2020). The initial and boundary conditions for WRF were provided by the global CCSM4 simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the horizontal resolution of RCMs in the paleoclimate context is increased to a level that convection is explicitly resolved (e.g. Velasquez et al, 2020b). This study shows the benefit of higher spatial resolution in particular over areas with complex terrain such as the Alps.…”
mentioning
confidence: 68%
“…Comparing LGM LGM with PD PD illustrates the entire effect of changes in the external forcing and in the surface conditions (sea level drop, land cover and northern hemispheric ice sheets). Note that the LGM LGM simulation is evaluated against proxy evidence (Prentice and Jolly, 2000;Wu et al, 2007;Kaplan et al, 2016) showing an improved LGM climate state in the WRF simulation (Velasquez et al, 2020b, a) compared to the driving CCSM4 simulations (Hofer et al, 2012a).…”
Section: Comm) Additionally the Lgmmentioning
confidence: 99%
See 1 more Smart Citation
“…Roucoux et al (2005) and Ludwig et al (2018) also suggested that this region during LGM sensu stricto was warmer and wetter than the end of Marine Isotope Stage 3 (MIS3, ca. 23 ka; Voelker et al, 1997;Kreveld et al, 2000) and the start of the Heinrich event 1 (H1, ca. 19 ka; Sanchez Goñi and Harrison, 2010;Álvarez-Solas et al, 2011;Stanford et al, 2011).…”
Section: Comparison and Discussion Of The Modelled And Reconstructed Climatementioning
confidence: 99%